Measuring the performance of library and information services in Universiti Tenaga Nasional Library / Roslah Johari - Roslah, Johari (2006)
This study is an exploratory study to assess the service quality of an academic library. The objectives are to examine the nature of the users' perceived expectations with regards to the quality of information services offered by the library, to assess and measure the users' opinion on the adequacy and inadequacy of the library in providing information services, to identify the service factors deem important to clients of the library, and to identify the problem areas of information services. The survey method is employed and the instrument used is the questionnaires which is based on a modified version of SERVPERF. The sample of respondents was randomly chosen from among the undergraduate and postgraduate students of the University, who visited the Library and were available during the period of data collection. A total of 300 questionnaires were distributed, out of which 274 (91%) usable questionnaires were returned. Generally, the results indicate that the respondents were satisfied with 22 service attributes, out of the 57 attributes under study. Most of the positive responses scored 'average' performance. The library services was rated as '7' on a 10-point scale, which shows an above 'average' quality score. The respondents in this study indicate being very satisfied with the peripheral services of UNITEN Library (100%). However, the respondents pointed out that there are sixteen aspects of the services of the library that should be improved which includes the library website, the user education programme, some issues on the waiting time for services, the OP AC services, the computer printers, and the staff assistance in helping users learn how to find information. Perceptions of service dimensions indicate that the respondents have chosen the 'tangibles' as the most important dimension, and 'empathy' as the least important.